Suberoylanilide hydroxamic acid (vorinostat) up-regulates progranulin transcription: rational therapeutic approach to frontotemporal dementia - Cenik, Basar; Sephton, Chantelle F; Dewey, Colleen M; Xian, Xunde; Wei, Shuguang; Yu, Kimberley; Niu, Wenze; Coppola, Giovanni; Coughlin, Sarah E; Lee, Suzee E; Dries, Daniel R; Almeida, Sandra; et al. (The Journal of biological chemistry, 2011)
Progranulin (GRN) haploinsufficiency is a frequent cause of familial frontotemporal dementia, a currently untreatable progressive neurodegenerative disease. By chemical library screening, we identified suberoylanilide hydroxamic acid (SAHA), a Food and Drug Administration-approved histone deacetylase inhibitor, as an enhancer of GRN expression. SAHA dose-dependently increased GRN mRNA and protein levels in cultured cells and restored near-normal GRN expression in haploinsufficient cells from human subjects. Although elevation of secreted progranulin levels through a post-transcriptional mechanism has recently been reported, this is, to the best of our knowledge, the first report of a small molecule enhancer of progranulin transcription. SAHA has demonstrated therapeutic potential in other neurodegenerative diseases and thus holds promise as a first generation drug for the prevention and treatment of frontotemporal dementia.